Self-Monitoring as a Personality Variable in Tinto’s Theory of Integration - Smith, Wade; Forbes, Sean; Robichaux-Davis, Rebecca; Guarino, Anthony J. (Advances in Social Sciences Research Journal, 2020)
One weakness of Tinto’s (1993) model is its inability to identify early dropouts (Webb, 1988), which may be due to the theory’s inattention to personality traits. Self-monitoring (Snyder, 1974) may be an important trait related to dropout. This study hypothesized low self-monitors, compared to high self-monitors would be more likely to (1) have higher initial commitment levels, (2) achieve higher academic integration, (3) accomplish greater social integration, and (4) persist in college. Path analysis confirmed all hypotheses. Self-Monitoring was demonstrated to be an important personal characteristic in Tinto's Theory. Application of theses findings are discussed.